Assessment of the knowledge of contamination-causing microorganisms in food and food products in Ilorin, Kwara State, Nigeria - OLUDAIRO, Oladapo Oyedeji; ZAKARIYA, Maryam Ebunoluwa; AIYEDUN, Julius Olaniyi; DAODU, Olufemi Babatunde; OLORUNSHOLA, Isaac Dayo; AKPABIO, Uduak (Ilorin Journal of Education, 2023)
The contamination of food and its products by microbial agents is a worldwide public-health concern. Many countries have documented significant increases in the incidence of diseases caused by microorganisms in food over the past few decades. This study focused on assessing the knowledge of the public on the microorganisms causing contamination in food and food products. Cross sectional study design was used in this study. The study population was members of the public in Ilorin, Kwara state, Nigeria. This was achieved by administering 223 structured questionnaire forms to willing members of the public in the Ilorin metropolis using stratified random sampling technique and undertaking desk reviews of responses. The result revealed that 67.7% of the respondents could not mention any food contaminants while 66.8% did not know anything about these contaminants while 95.5% only had superficial knowledge based on their response to questions about the subject matter. Male respondents and those above the age of 25 were adjudged to have more knowledge of microorganisms causing contamination in food while the knowledge of respondents with primary school certificate were lowest compared to those with other level of education. This strongly calls for an increase in public health education by all health professionals and the adoption of more innovative strategies for educating the public. There is a need for more advocacies and social mobilization by the government and non-governmental organizations with renewed vigour in the enforcement of public health regulations to safeguard members of society.